2021
DOI: 10.1002/ardp.202000419
|View full text |Cite
|
Sign up to set email alerts
|

3‐Aryl‐substituted imidazo[1,2‐a]pyridines as antituberculosis agents

Abstract: Novel inhibitors are needed to tackle tuberculosis. Herein, we report the 3‐aryl‐substituted imidazo[1,2‐a]pyridines as potent antituberculosis agents. A small library of 3‐aryl‐substituted imidazo[1,2‐a]pyridines was synthesized using direct arylation, followed by nitro reduction and finally Pd‐catalyzed C−N coupling reactions. The compounds thus obtained were evaluated against Mycobacterium tuberculosis H37Rv. Compound 26 was identified as an antituberculosis lead with a minimum inhibitory concentration of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…With an intent to explore other IPs, Karale et al reported a new potent anti-TB agent, 3-arylsubstituted IP, by replacing the extended amide side chain of Q203 with different substituted aryl or heteroaryl rings at the C-3 position. 55,56 Initially they found a hit compound with a trifluromethylphenyl substitution at the C-3 position (MIC 90 , 21.16 μM). Further SAR exploration of the aromatic ring on C-3, led to amine-substituted 3-arylimidazo[1,2-a]pyridine analog with promising activity against Mtb.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With an intent to explore other IPs, Karale et al reported a new potent anti-TB agent, 3-arylsubstituted IP, by replacing the extended amide side chain of Q203 with different substituted aryl or heteroaryl rings at the C-3 position. 55,56 Initially they found a hit compound with a trifluromethylphenyl substitution at the C-3 position (MIC 90 , 21.16 μM). Further SAR exploration of the aromatic ring on C-3, led to amine-substituted 3-arylimidazo[1,2-a]pyridine analog with promising activity against Mtb.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…3 in the original article). 55 Onajole et al reported IPA analogues containing cyclic aliphatic rings at the amide end and evaluated against DS H37Rv, V4207, MDR KZN494, MDR V2475, XDR R506, and TF274 strains of Mtb. 57 SAR studies revealed that the potency of analogues is dependent on the carbon spacer between amide nitrogen and the cyclic aliphatic ring.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%